User Interface Adaptation Using Web Augmentation Techniques: Towards a Negotiated Approach - Firmenich, Diego Andrés (2015)
The use of Web augmentation techniques has an impact on tasks of owners of Web sites, developers of scripts and end-users. Because the Web sites can be modified by external scripts, their owners might lose control about how Web site contents are delivered. To prevent this, they might be tempted to modify the structure of Web pages thus making harder to execute external scripts. However, communities of Web augmentation scripters are increasing since end-users still have needs not yet covered by Web sites. In this paper we analyze the trade-offs of the introduction of Web augmentation scripts. In order to mitigate some negative effects, such as the loss of control, we propose an approach based on negotiation and coordination between actors involved in the process. We present a set of tools to facilitate the integration of scripts and to foster their dissemination for the benefit of all actors involved.